I did it for the maktaaq: exploring Indigenous methodologies around beluga research in two communities in Inuit Nunaat - Sudlovenick, Enooyaq (2024)
Qilalugait, beluga whales (Delphinapterus leucas), are a circumpolar whale species. There are an estimated 21 distinct populations, many of which exist within Inuit Nunaat (homelands). Much of the current knowledge on beluga whales, outside of zoos and whales found dead on shore, come from samples obtained from Inuit harvests. These samples are often treated as representative of the populations from which they originate, and while statistical analyses can account for samples from wildlife of different ages or length, the local contexts are often not considered, which can affect data interpretation. In this thesis, I use a combination of qualitative and quantitative, as well as Indigenous and Western methods, to examine how local contexts can inform interpretation of wildlife health data. I and community-based collaborators conducted interviews in Arviat, NU and Tuktoyaktuk, NT in the appropriate language with active harvesters to determine similarities and differences in harvester preferences between the two communities. In the first publication, Chapter 3, I show how two holistic research methodologies, One Health and Indigenous methodologies, are similar yet fundamentally different in their origins and epistemologies, and in their application to wildlife research in Inuit Nunaat. In the second publication, Chapter 4, I compare beluga hunting seasons, size preferences, food preferences, and research priorities and observations between the two communities who harvest beluga and collect samples for this research. Finally, the last publication (Chapter 5) exemplifies how to consider local contexts when interpreting mercury concentration findings in beluga tissues. These findings show why and how different cultural preferences that are local to each region, community, and even family unit should be included when interpreting results of wildlife contaminant and health research. February 2025 Garfield Weston Family Foundation, ArcticNet Network of Centres of Excellence Canada, Nunavut Wildlife Management Board